Impact of respiratory bacterial infections on mortality in Japanese patients with COVID-19: a retrospective cohort study - Kensuke Nakagawara; Hirofumi Kamata; Shotaro Chubachi; Ho Namkoong; Hiromu Tanaka; Ho Lee; Shiro Otake; Takahiro Fukushima; Tatsuya Kusumoto; Atsuho Morita; Shuhei Azekawa; Mayuko Watase; et al. (BMC Pulmonary Medicine, 2023)
Abstract Background Although cases of respiratory bacterial infections associated with coronavirus disease 2019 (COVID-19) have often been reported, their impact on the clinical course remains unclear. Herein, we evaluated and analyzed the complication rates of bacterial infections, causative organisms, patient backgrounds, and clinical outcome in Japanese patients with COVID-19. Methods We performed a retrospective cohort study that included inpatients with COVID-19 from multiple centers participating in the Japan COVID-19 Taskforce (April 2020 to May 2021) and obtained demographic, epidemiological, and microbiological results and the clinical course and analyzed the cases of COVID-19 complicated by respiratory bacterial infections. Results Of the 1,863 patients with COVID-19 included in the analysis, 140 (7.5%) had respiratory bacterial infections. Community-acquired co-infection at COVID-19 diagnosis was uncommon (55/1,863, 3.0%) and was mainly caused by Staphylococcus aureus, Klebsiella pneumoniae and Streptococcus pneumoniae. Hospital-acquired bacterial secondary infections, mostly caused by Staphylococcus aureus, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia, were diagnosed in 86 patients (4.6%). Severity-associated comorbidities were frequently observed in hospital-acquired secondary infection cases, including hypertension, diabetes, and chronic kidney disease. The study results suggest that the neutrophil–lymphocyte ratio (> 5.28) may be useful in diagnosing complications of respiratory bacterial infections. COVID-19 patients with community-acquired or hospital-acquired secondary infections had significantly increased mortality. Conclusions Respiratory bacterial co-infections and secondary infections are uncommon in patients with COVID-19 but may worsen outcomes. Assessment of bacterial complications is important in hospitalized patients with COVID-19, and the study findings are meaningful for the appropriate use of antimicrobial agents and management strategies.